National Culture Values: reflections on formation process of future leaders in international economic cooperation - NIKOLIC, MARIJA; LA TORRE, MAURA; LALIĆ, GORAN (Journal of Education Culture and Society, 2020)
The trend towards foreign investments in Serbia has been in rapid progress in recent years. The biggest and most valuable numbers of investments are coming from Italy. The authors’ expectation is that the trend of Italian investments in future will continue; therefore it is of high importance for the representatives of both countries’ business sectors to under-stand and accept differences and similarities to the other country’s business culture. Research of cultural differences between two nations , which are considered like a frame of business culture, helps avoiding possible misunderstandings and improving business cooperation be-tween two countries. Having in mind students of economics and management, on one hand like future leaders of Italian and Serbian business and on other like representatives of the cur-rent education value system in the field of economics and management, this study consists of an application of the 7-D Hofstede Model. The application of the model takes place through the administration of two surveys done by students of Serbian Megatrend University, in Bel-grade, and Italian Università degli Studi Gabriele d’Annunzio, in Pescara